Alcohol use among adults in Kenya: Results from the National Non-Communicable Diseases Risk Factor survey, 2015. Issue 1 (2nd January 2019) - Pengpid, Supa; Peltzer, Karl
Abstract : The aim of this study was to assess the prevalence and correlates of alcohol use among Kenyan adults. We analysed data from the Kenya cross-sectional national Non-Communicable Diseases Risk Factor survey, 2015. The survey sampled 4 469 adults (median age 38.0 years, interquartile range = 23, age range of 18–69 years). Results indicate that 6.7% were hazardous or harmful alcohol users and 12.8% past month binge-drinkers. In adjusted logistic regression analysis, being male, middle aged, belonging to the Luhya or Kalenjin ethic group, tobacco use, and having hypertension increased the odds for hazardous or harmful alcohol use. Socio-demographic and health factors appear to influence risk for hazardous or harmful alcohol use among adults in Kenya.